Tsunami: Psychosocial aspects of Andaman and Nicobar islands. Assessments and intervention in the early phase - Suresh Bada Math ; Satish Chandra Girimaji ; Vivek Benegal ; G. S. Uday Kumar ; Ameer Hamza ; D. Nagaraja (International Review of Psychiatry, June 2006; 18(3): 233-239, 2006)
The aim of this paper is to describe the activities and observations of the team from National Institute of Mental Health and Neuro Sciences (NIMHANS) Bangalore, India in the Andaman and Nicobar Islands during the early phase of the Tsunami disaster in January and February 2005. The activities comprised mental health consultation at camps, community sensitization, mental health services to the students and children, teachers orientation sessions and training of nongovernmental organization [NGO] functionaries. Initial assessment reveals 58per cent of the population were suffering from significant mental health problems following the early phase of the disaster. This may increase in the aftermath of the early relief phase. Psychiatric morbidity is expected be around 25-30 per cent in the disillusionment phase. High resilience was seen in the joint family system of tribal Nicobarese during early phase of disaster. In developing countries like India, limited availability of mental health professionals and poor knowledge about disaster mental health among the medical and paramedical staff, may lead to poor psychosocial rehabilitation of the survivors. To respond to a high magnitude natural disaster like a tsunami, the disaster mental health team must be able to understand the local culture, traditions, language, belief systems and local livelihood patterns. They also need to integrate with the network of various governmental and non-governmental organizations to cater to the needs of the survivors. Hence the presence of a disaster mental health team is definitely required during the early phase of the disaster in developing countries.